Perceptions and Characterization of Local Knowledge on Soil Fertility Management by Maize Farmers in Central Benin - Codjo Jacques Houndete; Gaudence Julien Djego (European Scientific Journal, ESJ, 2023)
The problem of soil fertility leads farmers, according to their perception, to practice local and or introduced methods to manage the productivity of their farm. This study aimed to document local knowledge on soil fertility management by maize farmers in central Benin. A semi-structured survey was used to collect information from 1248 maize farmers in six communes in central Benin. The data were analyzed using descriptive statistics and multivariate analysis. Results showed that farmers consider declining soil fertility as one of the major constraints to maize production. About 45% of the farmers surveyed linked declining soil fertility to unsuitable fertilization practices. Maize farmers' soil fertility management methods are mainly based on synthetic chemical fertilizers such as urea (46%), NPK (15-15-15), NPKSB (14-23-14-5-1) and NPKSBZn (13-17-17-0.5-2.5) and Triple Superphosphate (45% P2O5). The application rates differed according to the type of fertilizer. Socio-demographic characteristics such as area planted, age, experience in maize production, membership in a farmer's organization, level of education, gender and income level of the farmer significantly determine the type of soil fertility management method practiced. These factors should be taken into account by extension programs.